Analisis Perbandingan Algoritma Supervised Learning untuk Prediksi Kasus Covid-19 di Jakarta - Septhiani, Angeline; Hendry, H (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2023)
Coronavirus disease or called COVID-19 is a pandemic according to World Health Organization (WHO) in February. The virus gives several symptoms, such as cough, asthma, and fever. The data and information are the important part of making a good decision. Those data need to be processed and analyzed to be useful information. In this research, the data will be used to predict the COVID-19 issue in Jakarta, using several supervised learning algorithm models, such as K-Nearest Neighbors, Neural Network, Linear Regression, Support Vector Machine, and Random Forest. Using 10 Fold Cross Validation in model testing and T-Test to get the model with the best accuracy. According to this research, the algorithm that has the best accuracy is K-Nearest Neighbors with the lowest RMSE, 1096.188 +/- 365.077 (micro average: 1149.601 +/- 0.000).